2006
DOI: 10.1016/j.chembiol.2006.06.015
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biocombinatorial Synthesis of Lipopeptides by COM Domain-Mediated Reprogramming of the Surfactin Biosynthetic Complex

Abstract: The intermolecular communication within NRPS complexes relies on the coordinated interplay of donor and acceptor communication-mediating (COM) domains. In this study, the potential of COM domains was exploited in vivo by establishing a system for the true biocombinatorial synthesis of lipopeptides via directed reprogramming of a natural NRP biosynthetic assembly line (i.e., surfactin). By means of COM domain swapping, these experiments verified the decisive role of COM domains for the control of protein-protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 30 publications
1
64
0
2
Order By: Relevance
“…This strongly suggests the N terminus of ZmA initially contained a fatty acid, along with D-Asn. Finally, Chiocchini and colleagues and Hahn and Stachelhaus have shown that E domains and C domains that interact with each other contain communication domains that function as sites of specific protein-protein interactions between E and C domains on different NRPS polypeptides (7,15,16). Analysis of the C terminus of the E domain of ZmaO and the N terminus of ZmaK identified sequences consistent with communication domains (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…This strongly suggests the N terminus of ZmA initially contained a fatty acid, along with D-Asn. Finally, Chiocchini and colleagues and Hahn and Stachelhaus have shown that E domains and C domains that interact with each other contain communication domains that function as sites of specific protein-protein interactions between E and C domains on different NRPS polypeptides (7,15,16). Analysis of the C terminus of the E domain of ZmaO and the N terminus of ZmaK identified sequences consistent with communication domains (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…Chiocchini et al (2006) show that a heterologous COM domain pair can replace the native COM domain pair. Indeed, the replacement of COM…”
Section: Combinatorial Synthesis Of Lipopeptidesmentioning
confidence: 99%
“…Chemoenzymatic approaches were used to characterise the specificity of the thioesterase domain. Different heptapeptides were synthesised by chemical means, and a thioesterase domain was cloned and produced as an isolated enzyme (Chiocchini et al 2006).…”
Section: The Surfactin Operonmentioning
confidence: 99%
“…The modular organization of protein domains in NRPSs has stimulated efforts to swap genes encoding heterologous domains into NRPSs with the goal of producing nonnatural variants of the original small-molecule product (3,4). Although limited success has been achieved with the production of nonribosomal peptide (NRP) variants (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), the resultant chimeric NRPSs are usually nonfunctional or heavily impaired, often yielding too little of the new product to make production feasible. It is not yet known why chimeric NRPSs suffer large reductions in activity, although it is likely that domain swapping disrupts quaternary interactions between protein domains in the assembly line (15).…”
mentioning
confidence: 99%